Therapeutic Benefit of Dillenia indica in Diabetes and Its Associated Complications - Parul Kamboj; Narayan C. Talukdar; Sanjay K. Banerjee (Journal of Diabetes Research)
Diabetes, a metabolic disorder characterized by elevated fasting blood glucose levels, affects nearly 8% of the world population and was predicted that it would be the top seven leading cause of death in the next ten years. The incidence of diabetes and its morbidity are increasing rapidly in developing countries due to lifestyle change and intake of high-calorie diet occurring with urbanization. Medicinal plants and their products have been proven to be effective, less expensive, and safe for the treatment and prevention of diabetes. Although several medicinal plants known for the antidiabetic property are reported in the ancient medical textbook, there is always a scope to identify and validate less explored medicinal plants that are still practiced regularly by local and tribal people since ancient times. Here, in the present article, we would like to review a less explored medicinal plant, Dillenia indica, which has promising effects in treating diabetes and other diabetic-associated complications. In spite of its wide use in the Northeast region of India as traditional medicine, there is only one clinical study where the antidiabetic potential of the fruit powder has been shown. Further well-designed animal and human studies are needed to confirm the role of Dillenia indica in diabetes and its associated complications.